Privacy glass enterprise : smart window / Nur Ashiqin Zulkifli ... [et al.] - Zulkifli, Nur Ashiqin; Mohamad Yassin, Norshahirah; Alias, Nur Maisarah; Mohd Sukaimi, Muhamad Zulhilmi; Kamarulzaman, Nur Farah Arissa (2017)
Privacy Glass Enterprise is accompany that focuses on windows for privacy. We specialize in providing quality windows. We also used quality material to attract customers.